2000
DOI: 10.1002/1097-4652(200011)185:2<269::aid-jcp12>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Celtix-1, a bromodomain protein interacting with the transcription factor interferon regulatory factor 2

Abstract: Transcriptional control at the G1/S-phase transition of the cell cycle requires functional interactions of multimeric promoter regulatory complexes that contain DNA binding proteins, transcriptional cofactors, and/or chromatin modifying enzymes. Transcriptional regulation of the human histone H4/n gene (FO108) is mediated by Interferon Regulatory Factor-2 (IRF-2), as well as other histone gene promoter factors. To identify proteins that interact with cell-cycle regulatory factors, we performed yeast two-hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…We have shown that, in addition to BRCA1, BRD7 is also able to recruit the transcription factor Oct-1 to the ESR1 promoter. A previous study showed that BRD7 could also bind the transcription factor IRF2 (13). It is possible that the role of BRD7 within the Swi/ Snf complex is to provide specificity by selectively recruiting specific transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that, in addition to BRCA1, BRD7 is also able to recruit the transcription factor Oct-1 to the ESR1 promoter. A previous study showed that BRD7 could also bind the transcription factor IRF2 (13). It is possible that the role of BRD7 within the Swi/ Snf complex is to provide specificity by selectively recruiting specific transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Kzhyshkowska et al (2003) suggested that BRD7, together with E1B-AP5, which belongs to the family of hnRNP-u, functioned as an inhibitor of basic transcription in several viral and cellular promoters in the nucleus. Staal et al (2000) reported that the BRD7 protein (celtix-1) interacted with interferon regulatory factor 2 (IRF-2) in the nucleus and was associated with transcriptionally active chromatin in situ. In addition, Kim et al (2003) reported that BP75, the most homologous gene of BRD7, was found to bind dishevelled-1 and enhance Wnt signaling by inactivating glycogen synthase kinase-3 beta.…”
Section: Introductionmentioning
confidence: 99%
“…The variation in the ΔC p values between specific and nonspecific BrD3-acetyl-histone complexes determined experimentally was compared with the values calculated based on the change in solvent-exposed surface area [47][48][49]: (5) where ΔA np and ΔA p are the changes in nonpolar and polar surface area, respectively. The ΔC p values from nonspecific to specific range from -400 to -1600 J/K · mol, indicating significant variation in the hydration of the BrD-histone interface.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence indicates that large multiprotein chromatin remodeling complexes regulate transcription by localizing to certain chromatin sites through the interaction of bromodomain (BrD) 1 proteins with acetylated nucleosomes [1][2][3][4][5][6][7]. The BrD is a protein motif, approximately 100 amino acids in length, primarily associated with targeting subunits of chromatin remodeling complexes [8].…”
Section: Introductionmentioning
confidence: 99%